RESISTANCE OF LOCAL BANANA VARIETIES TO FUSARIUM WILT DISEASE - Mariana, Mariana; Budi, Ismet Setya (TROPICAL WETLAND JOURNAL, 2017)
Fusarium wilt is one of the important banana diseases that lead to low quality and quantity of banana production. The objective of this study was to examine and study the resistance of some local banana varieties to fusarium wilt. Pathogens were isolated from the weevil of kepok banana (saba banana) that showed severe symptoms of Fusarium wilt. The inoculum was prepared by propagating the pathogens on Potato Dextrose Agar (PDA) medium. Inoculation was carried out using mycelium fragment suspension (12 mg hyphae mL-1 tween 20 0.05%). The roots of the two-week Ambon banana were injured and immersed in the suspension. Pathogens were determined using Koch's postulates. The varieties tested were seven (7) local banana varieties grown in South Kalimantan. Levels of resistance were determined based on the scale of Leaf Symptom Index (LSI). The pathogens were identified as Fusarium oxysporum f.sp. cubense. The results showed that there were differences in the levels of resistance; Kepok banana (highly susceptible); yellow Ambon, Awa, Susu, Mahuli and Talas bananas (susceptible), and Manggala banana (tolerant). Keywords: fusarium wilt, local bananas, resistance